Effect of Blanching and Probiotic to Eggplant (Solanum Melongena) Fermentation - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
The eggplant (Solanum melongena, L.) is a good source of minerals and vitamins. Being rich in fiber and having low lipid content, it contains a variety of phytochemicals, such as polyphenols, which provide important health benefits. However, the short shelf life of eggplant can be a major cause of postharvest losses especially during peak harvesting season. Fermentation is one of the most convenient technologies for the production of shelf stable food product. The objective of this study was to evaluate different aspects affecting to the fermentation of eggplants such as concentration of CaCl2, temperature and time for blanching; effect of ratio Lactobacilus acidophillus to the antioxidant of fermented eggplant. Results showed that eggplants should be blanched in hot water 95oC in 10 seconds with the present of 2.0% CaCl2. Moreover, the fermentation process for pickle eggplants had the best antioxidant by Lactobacilus acidophillus at ratio 1.5 x 108 cells/ml. Blanching and fermentation had significantly affected to antioxidant capacity and firmness of pickle eggplants.Keywords: Eggplant, Pickle, Fermentation, Blanching, Lactobacilus acidophillus, Antioxidant.